2021
DOI: 10.1007/s00068-021-01808-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and skills of emergency physicians in managing traumatic dental injuries

Abstract: Purpose Emergency departments are frequently confronted with traumatic dental injuries (TDIs). The prognosis of the injured tooth is related to early dental trauma management. For this reason, physicians must be familiar with the appropriate management of TDI. This study aimed to investigate the knowledge and skills of German emergency physicians regarding TDI. Methods An electronic questionnaire was sent to 438 emergency departments throughout Germany. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The ideal treatment of tooth avulsion that can ensure long-term success is immediate replantation. Transport media are used to maintain the viability of periodontal ligament cells, increase their survival, and prevent any damage that could cause future tooth loss, such as ankylosis and resorption [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal treatment of tooth avulsion that can ensure long-term success is immediate replantation. Transport media are used to maintain the viability of periodontal ligament cells, increase their survival, and prevent any damage that could cause future tooth loss, such as ankylosis and resorption [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In the specialized literature, the percentage of correct answers regarding physiological serum and milk as the storage medium varies from 100% for milk in the United Arab Emirates [21], to 74.7% among Italian dentists [24], 15.8% correct answers for dentists in China [27], and 11.2% in Germany [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is evidence that physicians' assistants have limited knowledge of oral health and that hands-on training can improve knowledge [2]. A study on emergency room doctors, where 1.5 million dental-related visits occur across the United States (US) each year, showed that 60% reported "no or insufficient" knowledge of managing oral health emergencies [3]. Suffice it to say that oral health knowledge is extremely limited outside of the dental profession.…”
Section: Introductionmentioning
confidence: 99%